Pengaruh Ukuran Perusahaan, Leverage dan Profitabilitas Terhadap Pengungkapan Tanggung Jawab Sosial Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2014-2016 - Iszatun Azmi Eka Fatma (Universitas Muhammadiyah Semarang, 2019)
This study aims to examine the effect of company size, leverage, and profitability on social responsibility disclosure in manufacturing companies listed on the Indonesia Stock Exchange (BEI) 2014-2016. The sample used in this study is manufacturing companies listed on the Indonesia Stock Exchange ( IDX) based on predetermined criteria. The sampling method used was purposive sampling and 153 data were selected as samples, and hypothesis testing in this study using multiple regression analysis. The results of this study indicate that the independent variable company size and leverage partially have a significant effect, but the independent variable partially profitability does not have a significant effect on social responsibility disclosure. And the test results of the coefficient of determination show a number of 0.103, this indicates that simultaneously the independent variables of company size, leverage, and profitability are able to explain the dependent variable social responsibility disclosure as much as 10.3%, while the remaining 89.7% is explained by other variables.